2007
DOI: 10.2224/sbp.2007.35.9.1189
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Personality and Motivation on Exercise Participation and Quality of Life

Abstract: The major purpose of this study was to identify the effects of personality on individual exercise motivation and exercise participation, which then influences quality of life. A comprehensive model was developed, based on an extensive literature review, and empirically tested using members of fitness centers from Taiwan, Europe and the United States as respondents.The results indicate that individuals with a positive personality tend to have higher levels of exercise motivation and exercise participation. Pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 53 publications
1
15
0
7
Order By: Relevance
“…Although the mechanisms between HRQoL and women cancer screening are still unclear, it is possible that women with better HRQoL may possess the characteristics of optimistic personality and greater self-efficacy that will encourage the engagement in healthy behaviors [48,51,52]. Such health promoting and preventive health behaviors might lead to increased participation in screening activities for breast and cervical cancer [53].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms between HRQoL and women cancer screening are still unclear, it is possible that women with better HRQoL may possess the characteristics of optimistic personality and greater self-efficacy that will encourage the engagement in healthy behaviors [48,51,52]. Such health promoting and preventive health behaviors might lead to increased participation in screening activities for breast and cervical cancer [53].…”
Section: Discussionmentioning
confidence: 99%
“…Having a specific plan for implementing a general intention may also differentiate those who exercise from those who do not (Chasteen, Park, & Schwarz, 2001;Gollwitzer, 1999;Schwarzer, 2008). Furthermore, personality variables that correlate with self-efficacy beliefs, especially conscientiousness (Pearman & Storandt, 2005), also correlate with physical activity and exercise adherence (Conner, Rodgers, & Murray, 2007;Huang et al, 2007;Ingledew, Markland, & Sheppard, 2004;Rhodes & Smith, 2006). Integrative models should consider a number of characteristics that combine to produce active lifestyles in older adults (Rhodes, Couneya, Blanchard, & Plotnikoff, 2007).…”
Section: Positive Attitudes and Beliefsmentioning
confidence: 99%
“…Specifically, those who had higher baseline conscientiousness demonstrated to be more physically active at the follow-up, independent of baseline MVPA and other personality types (as well as other covariates). Previous research has suggested conscientiousness to be most strongly related to participation in exercise behavior because of the goal to protect health (Huang, Lee, & Chang, 2007). Additionally, individuals with higher levels of conscientiousness may be more dutiful, orderly, and self-disciplined (McCrae & Costa, 1995), all of which may play an important role in behavioral self-regulation.…”
Section: Discussionmentioning
confidence: 99%